Rural Agricultural Marketing – Issues & Strategies: Enhancing Rural Agricultural Marketing Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Around the world, four billion people live in poverty and marketing firms are still struggling to turn them into customers. After the Green Revolution in India, the people living in rural areas are started to use consumable and non consumable products in large quantity. This paper studies the various factors affecting Agricultural Productivity. It also provides suggestions for an effective Infrastructure in rural agricultural marketing. Strategies are framed for improving marketing. The key to face challenges is to understand the market, the consumer need and behavior.